What did we learn about tocilizumab use against COVID-19? A single-center observational study from an intensive care unit in Serbia - Adzic-Vukicevic, Tatjana; Markovic, Dejan; Reljic, Aleksandar; Brkovic, Voin (Frontiers in Medicine, 2023)
Background: Selection of effective and safe therapy for management of patients with coronavirus disease is challenging. Tocilizumab has emerged as a potential treatment option for COVID-19. Several aspects regarding Tocilizumab treatment remain uncertain, such as the optimal timing for its administration and the safety profile, including the potential risk of infections. The aim of the study is to present the clinical characteristics of patients with COVID-19 following the application of Tocilizumab.Methods: Retrospective analysis of 121 patients with severe forms of COVID-19 previously treated with Tocilizumab was conducted. All patients were admitted to intensive care units (ICUs).Results: Of 121 patients, majority were men 72 (59.5%) with median age at presentation 65± 13 years. Only 9 (7.43%) patients were without comorbidities, while the 112 (92.55%) had two or more comorbidities. Almost all patients 120 (99.2%) needed oxygen therapy, such as nasal cannulas in 110 (90.9%), high flow nasal catheter (HFNC) in 4(3.3%), continuous positive airway pressure (CPAP) in 5(4.1%) while one patient was intubated at time of hospital admission. Average time from Tocilizumab application to admission to ICU was 3 days. During clinical deterioration almost half of the patients were intubated 57 (47.1%), and 52 (82.5%) of these intubated patients (p< 0.001) had lethal outcome. The most significant predictors for lethal outcome according to multivariate analysis were diabetes mellitus (p<0.001), followed by a subsequent elevation in C-reactive protein levels (CRP) (p<0.002) and ferritin (p<0.013) after Tocilizumab application. Blood stream infections were found in 20 (16.5%), most frequently with Gram negative pathogens like Acinetobacter spp in 12 (18.6%) patients, Klebsiella spp in 6 (8%) patients and Pseudomonas spp in 2 (3.2%) patients. Urine culture isolates were found in 9 (7.43%) patients, with Candida spp most frequently isolated in 7 (5.8%) patients. Significantly lower survival was shown in patients with proven infection.Conclusions: Tocilizumabʼs benefit in our study was not found. High mortality rate among intubated patients after Tocilizumab use, suggests appropriate patient selection, monitoring and emphasis risk of superinfections. Diabetes mellitus, increased levels of CRP and ferritin were identified as the most significant predictors of poor outcome in contrast to increased levels of IL-6.